Determining building-specific wind pressure coefficients to account for the microclimate in the calculation of air infiltration in buildings. Issue 3 (4th May 2021) - Charisi, Stergiani; Waszczuk, Milosz; Thiis, Thomas K.
ABSTRACT: Wind pressure coefficients ( Cp ) are important for the correct calculation of the air infiltration of a building. Cp depends on wind direction, position on the building façade and site exposure, and is therefore influenced by the microclimate. The external coupling between building energy simulation (BES) software and computational fluid dynamics (CFD) pre-processing allows calculating building-specific wind pressure coefficients that can account for the microclimate. BESs have been performed in order to calculate the infiltration rate of a reference building using surface-averaged Cp values from two different sources; a standard database and CFD simulations from OpenFOAM. Tracer gas measurements were performed in the reference building in order to validate the simulation results. The results show the coupled CFD/BES method gives building-specific Cp values that represent adequately the microclimatic conditions, leading up to 45% more accurate air infiltration rates compared to conventional methods.